2022
DOI: 10.1111/1462-2920.16031
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit affects inter‐kingdom microbial connections in plant rhizosphere

Abstract: The frequency and severity of drought are increasing due to anthropogenic climate change and are already limiting cropping system productivity in many regions around the world. Few microbial groups within plant microbiomes can potentially contribute towards the fitness and productivity of their hosts under abiotic stress events including water deficits. However, microbial communities are complex and integrative work considering the multiple co-existing groups of organisms is needed to better understand how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 69 publications
3
16
0
Order By: Relevance
“…Plant cultivars are known to have a strong influence on rhizobacterial networks and keystone species ( Jiang et al, 2017 ). Moreover, a previous study reported that water deficit changed the stability of plant rhizosphere networks ( Bazany et al, 2022 ). In the current study, the microbial co-occurrence network of 101-14 was more complex than that of 5BB under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Plant cultivars are known to have a strong influence on rhizobacterial networks and keystone species ( Jiang et al, 2017 ). Moreover, a previous study reported that water deficit changed the stability of plant rhizosphere networks ( Bazany et al, 2022 ). In the current study, the microbial co-occurrence network of 101-14 was more complex than that of 5BB under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between plants and the soil microbiomes that colonize the rhizosphere and root system is considered a key factor in the rapid adaptation of plants to soil environmental stress (Pascale et al, 2019). However, changes in the rhizosphere microbial community under drought stress depend on the influence of the host plant and the surrounding soil (Bazany et al, 2022). Differences in plant varieties (genotypes) can lead to different levels of drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The archaeal family Nitrososphaeraceae is steadily represented but derived from soil (Wolfgang et al, 2020 ). Protists play a pivotal role in shaping sugar beet rhizosphere microbiomes (Bazany et al, 2022 ), but are rarely investigated on metagenomic levels. Interestingly, sugar beet rhizospheres were repeatedly reported to display a comparable (Mendes et al, 2011 ), or even higher bacterial alpha diversity than surrounding bulk soil in the early seedling stages (Zachow et al, 2014 ; Wolfgang et al, 2020 ), but also in the rhizosphere of pre-harvest taproots (Cardinale et al, 2020 ), while also significant lower rhizosphere alpha diversity compared to bulk soil was reported (Cui et al, 2022 ).…”
Section: Part I: Microbial Journeys On and In Sugar Beets: From Seed ...mentioning
confidence: 99%